Pengaruh Perbandingan Sosial Pada Teman Sebaya Terhadap Citra Tubuh Siswa SMPN 6 Makassar - Nabilah Risky Ary Budianto; Harlina Hamid; Ahmad Ridfah (J-CEKI : Jurnal Cendekia Ilmiah, 2023)
This study aims to determine whether there is an influence of social comparisons between peers on the body image of SMPN 6 Makassar students. The method used in this research is quantitative. Measuring tool used in this study is the social comparison scale on peers and body image. The subjects of this research were 286 students of SMPN 6 Makassar. The results of the hypothesis test showed that the value of p = 0.000 (p <0.05), the correlation value = -0.816, and the value of Rsquare = 0,666. Based on these results, there is an influence of social comparisons between peers on the body image of SMPN 6 Makassar students with a negative correlation value, meaning that the higher the social comparisons between r peers, the lower the body image and social comparisons. peers have an influence of 66.6% on body image. student